PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA - Septian Wahyudi (UIR Press, 2021)
Product quality is closely related to purchasing decisions, where product quality is one aspect of consumer considerations in making purchasing decisions, quality products will lead to consumer satisfaction which in turn will make these consumers loyal to the product. A company should be able to provide quality in accordance with the wishes and needs of consumers by paying attention to quality standards in the market. This is intended so that the quality provided by the company is not less competitive than the products of other competing companies.